137k views
2 votes
2(x−3)=8(x−6) what is the answer please take your time and get it correct

1 Answer

2 votes

Answer: x=7


Step-by-step explanation: First to get rid of the parentheses we must multiply everything times 2 in the parentheses. Then we must also do the same with the other parentheses multiply everything by 8.

2(x−3)=8(x−6)

2x-6=8x-48

Then we subtract 8x from both sides.

2x-6=8x-48

-6x-6=-48

Then add 6 to both sides

-6x-6=-48

-6x=-42

Finally divide both sides -6

-6x/-6=-42/-6

x=7

Hope this helps!


User HeyAlex
by
5.9k points